Outlays on legal aid in Poland. Could we get more out of it? (Economic and Political Thought, 2017)
SummaryThis article deals with estimates of the costs of the informal legal aidsystem in Poland along with estimates of a possible institutional reform ofthe system. Due to the lack of official data it was necessary to apply novelprocedures of measurement. Two approaches were used: a quasi-market anda quasi-budget one. In line with the first approach the costs of the informallegal aid system in 2012 were estimated at 540 million PLN. Under the otherapproach, depending on data availability on particular legal aid providers,three specific procedures of measurement of unit costs were employed, whichin combination with precise information on the total number of legal aidproviders by type, enabled estimation of the total costs of the informal system.Implementation of the quasi-budget approach resulted in the estimation ofthe annual total costs of the present system at the level of 514 million PLN(ca 170 million USD). Such a result is thus close to the quasi-market estimate,which seems to raise the credibility of the performed computations. Finally,one is allowed to formulate a conclusion that annual cost of the functioningof the informal system of legal aid in Poland was well above 500 million PLN,as the calculus was carried out with minimalistic cost assumptions. The articlealso attempts at estimating the costs of an institutionalised legal aid reformin Poland. A main premise behind adequate computations is the observationthat the new system will not replace the existent one but will just supplementit. This is so because a complete replacement of the present informal systemwith a new formal one would prove economically ineffective as this act wouldbe tantamount to depriving the already well-functioning providers of theright to give legal support to those in need. A key issue for estimating thecosts of the reform consists in establishing the amount of unmet demand forlegal aid as well as the outflow of legal aid recipients from the old to the newsystem, including outflows from the commercial sector of legal advice. Usingdeductive analysis, supported by data and conclusions drawn on the basis ofthe national questionnaires into legal aid recipients and providers, the upperestimate of the total costs of the reform was fixed at the level slightly below180 million PLN (ca 60 million USD).